Trauma and Psychological Self-Destruction: An Overview of the Exasperating Emotional Imbalance in K R Meera’s The Unseeing Idol of Light - S, Sruthi; A R, Savitha (The Grove - Working Papers on English Studies, 2023)
The present article discusses trauma and its impact on human emotions, particularly on women, in literature, with a focus on K R Meera’s novel, The Unseeing Idol of Light. The research paper highlights the rise of trauma theory in literature and explores the cultural and psychological influence of trauma in literature. It also analyses the characters in the novel through the lens of emotional imbalance and interdependency and examines the interrelation between vision, love, and trauma. The prevalence of negative emotions over positive emotions in the novel has been discussed. The paper emphasises the importance of mental stability in contemporary society and discusses various themes such as psychic changes, loss, longing, and transformation. The researcher aims to analyse and relate the selected work with critical thinking to shed light on the cultural and psychological impressions of literature.